Lymphocyte-to-high-density lipoprotein ratio and mortality in asthma patients: a novel immunoinflammatory biomarker with nonlinear association - Tian, Tu-Lei; Wu, Guan-Wei; Xie, Mei-Ling; Qu, Xiang-Kun; Wang, Xiao-Tong; Sun, Chang-Lu (Frontiers in Medicine, 2025)
BackgroundThe lymphocyte-to-high-density lipoprotein ratio (LHR), a novel biomarker reflecting systemic inflammation and immune status, has been widely studied in various diseases. However, its association with mortality risk among asthma patients remains unexplored.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999–2018, including 5,323 adult asthma patients. Mortality outcomes were ascertained through linkage with the National Death Index (NDI) up to December 31, 2019. Cox proportional hazards models and Fine-Gray competing risk models were employed to examine the association between LHR and mortality risks. Dose–response relationships were assessed using restricted cubic spline analyses.ResultsOver a mean follow-up period of 106.95 months, 724 all-cause deaths (13.6%) were recorded. After multivariable adjustment, a one-unit increase in log-transformed LHR was associated with reduced risks of mortality: 18% for all-cause (HR = 0.82, 95% CI: 0.74–0.91), 21% for cardiovascular disease (CVD) (HR = 0.79, 95% CI: 0.65–0.96), and 41% for chronic lower respiratory disease (CLRD) (HR = 0.59, 95% CI: 0.45–0.77). Restricted cubic spline analyses showed an L-shaped association of LHR with all-cause and CLRD mortality, with inflection points at 1.78 and 1.52, respectively. For CVD mortality, a linear association was observed. Competing risk models further confirmed the association of LHR with reduced CLRD mortality (SHR = 0.64, 95% CI: 0.46–0.88), while the association with CVD mortality was no longer significant (SHR = 0.85, 95% CI: 0.70–1.03).ConclusionLHR is nonlinearly associated with all-cause and CLRD mortality and shows a significant inverse association with CLRD mortality risk. These findings were further validated using competing risk models, highlighting the robustness of the results.